Without Rethinking Colonialism and Racialization, a Sustainable Future is Not Possible - Marina Gržinić (Lateral)
In this article, I talk about the performances of global capitalism, its relation to colonization and racialization, and the ways it hinders the well-being of vulnerable bodies. An understanding of the relation between post-colonialism and post-socialism is crucial to this discussion. I therefore start from a territory that is no longer conceivable today, namely former Eastern Europe and its post-socialism of 1990. I then proceed to discuss the relation of post-socialism to post-colonialism and capitalism. I conceptualize and discuss a diagram that illustrates the relations between the former East, the West, the North, and the South, and in particular, the relation between labour and capital and between capitalism and colonialism across these territories. I suggest that if we are to dismantle imperialism, that is, terminate capitalist colonialism, we need to rethink the racial/colonial divide and the imperial/colonial divide.